SISTEM INFORMASI E-LIBRARY MENGGUNAKAN METODE WEB ENGINEERING - Ihsan Alvindra; Cindi Wulandari; Bunga Intan (Jurnal Komputer dan Teknologi, 2026)
A digital library information system (E-Library) offers a solution to the challenges of library data management—previously handled manually—which often resulted in disorganized records and difficulties in retrieving information regarding books and members. This study aims to design and develop an E-Library information system for SMP Negeri Purwodadi using the Web Engineering method, encompassing user requirements analysis, system design, implementation, and testing. The Laravel framework serves as the core technology for building a robust and efficient backend system, while Black Box Testing ensures the system operates in accordance with user needs. The results demonstrate that the system enables students and staff to access book data, search collections, and manage member information digitally via a user-friendly interface. Testing confirms that the system meets functionality and reliability standards. This development fosters a more integrated, efficient, and secure library management process, thereby enhancing the quality of school library services and supporting digital transformation in education.